O Lyceu Franco-Brasileiro São Paulo - Vercesi, Maria Elena de Abreu (2010)
This dissertation aims to observe the criation, institutionalization, and setting up processes of the Lyceu Franco-Brasileiro São Paulo, known as Liceu Pasteur, and its position within the private high-school field during the first three decades of the 20th century, when the interests in international relations and national political strugles were established. It has been observed how cultural policy in international relations was structured as an important instrument which aimed the interests of the two involved agents, São Paulo oligarchic elite and France. For the execution of the Lyceu a statute was elaborated, which is considered a priviliged source for its study, since it presents the criation set of ideas and how the execution should be carried on. The Departamento Nacional de Ensino (National Department of Teaching) acts and reports relating to anual exams are also priviliged sources, reporting the choice of subjects, number of students and teachers names, and making possible to compare the statute determinations. The school books imported from France and used during the first years after the Lyceu was set up reveal, from their content analysis, the action of French cultural policy. This research has studied the reason why the Lyceu Franco-Brasileiro São Paulo, during its first decades, presented a crisis of the French school model, which resulted in the small number of student applications